Modern imaging of pituitary adenomas. Issue 2 (April 2019) - Bashari, Waiel A.; Senanayake, Russell; Fernández-Pombo, Antía; Gillett, Daniel; Koulouri, Olympia; Powlson, Andrew S.; Matys, Tomasz; Scoffings, Daniel; Cheow, Heok; Mendichovszky, Iosif; Gurnell, Mark
Abstract : Decision-making in pituitary disease is critically dependent on high quality imaging of the sella and parasellar region. Magnetic resonance imaging (MRI) is the investigation of choice and, for the majority of patients, combined T1 and T2 weighted sequences provide the information required to allow surgery, radiotherapy (RT) and/or medical therapy to be planned and long-term outcomes to be monitored. However, in some cases standard clinical MR sequences are indeterminate and additional information is needed to help inform the choice of therapy for a pituitary adenoma (PA). This article reviews current recommendations for imaging of PA, examines the potential added value that alternative MR sequences and/or CT can offer, and considers how the use of functional/molecular imaging might allow definitive treatment to be recommended for a subset of patients who would otherwise be deemed unsuitable for (further) surgery and/or RT.